The Influence of Financial Distress, Growth Opportunities, and Female Directors on Accounting Conservatism - Agustina, Fitria Fertha; Utami, Tika Putri (Faculty of Economics and Business, Hasanuddin University, 2025)
This study aims to test and analyze the effect of the level of financial difficulty, growth opportunities, and female directors on accounting conservatism in manufacturing companies listed on ISSI during the period 2019-2022. This study uses a quantitative approach and uses secondary data from annual financial reports. Data analysis was carried out using multiple linear regression , analysis and testing were carried out using the SPSS 25 statistical tool. The results of the study indicate that the level of financial difficulty has a negative effect on accounting conservatism with a significance value of 0.003 <0.05, meaning that the higher the level of financial difficulty, the lower the level of accounting conservatism. Conversely, growth opportunities value with a significance of 0.007 < 0.05 and female directors with a significance value of 0.028 < 0.05 indicate a positive influence on accounting conservatism, meaning that growth opportunities and female directors can encourage companies to implement more accounting conservatism. This study providespractical implications regarding considerations of the application of accounting conservatism in companies according to company conditions.